Trading beyond the matrix : the red pill for traders and investors - Tharp, Van K. (Hoboken, New Jersey : John Wiley & Son, Inc., 2013)
How to transform your trading results by transforming yourself In the unique arena of professional trading coaches and consultants, Van K. Tharp is an internationally recognized expert at helping others become the best traders they can be. In Trading Beyond the Matrix: The Red Pill for Traders and Investors, Tharp leads readers to dramatically improve their trading results and financial life by looking within. He takes the reader by the hand through the steps of self-transformation, from incorporating "Tharp Think"--Ideas drawn from his modelling work with great traders-making
Level I: Transformation of the Trading Game -- Level II: Understanding the Matrix and Reprogramming Yourself -- Level III: Trading Beyond the Matrix Your Personal Application of This Material. -- Section I. Transformation of the trading game: Understanding the basics. -- Section II. Psychological transformations to help you function at a superior level within the matrix -- Section III. Moving Beyond the matrix by transforming for your level of consciousness.
Includes index.
Keywords: BUSINESS AND ECONOMICS